Consulting as Part of the Infrastructure Supporting Small and Medium-Sized Businesses in Russia - E. A. Kuklina (Управленческое консультирование, 2019)
In the modern world, consulting has frmly gained its position in the market as a “doctor in the business world”, performing services at all stages of an organization’s life cycle — creating, developing, and solving not only situational but and strategic, innovative challenges. The emergence of such commercial services as consulting, of course, was inﬂuenced by the demand for specialists in various felds of activity, who were simply not available in the organization or keep them unprofitable due to the diﬀerence in the frequency of such services. However, in Russia there is a stereotype that non-material resources are much inferior to material ones and the use of consulting services is a waste of money. In fact, high-quality work of specialists can provide a business with an increase in the efciency of economic activity at times. The work of the consultant is based on the scientifc organization of labor, system analysis, evidence-based decision-making methods. It is also worth noting that the consultant soberly assesses the situation in the organization and treats it impartially. The activities of consultants today is one of the structural components of the infrastructure to support small and medium-sized businesses operating on commercial terms. Indeed, the payment of the work of a consultant in an organization is high, but it is worth considering that such work can bring an organization greater proft in the long term and short term. Also, the work of a consultant can save you from many risks (fnes, legal fees, etc.). Foreign experience in using consulting services shows that European countries often resort to them and sometimes cooperate on an ongoing basis. In Russia, the situation is diﬀerent. Managers try to reduce transaction costs by avoiding these services. This article will analyze the situation of the market of consulting services in Russia, its development and prospects, the statistics is given at the end of the 2018th year.